Implementation of the anti-child trafficking framework in Nepal: an impaired diffusion process. Issue 2 (17th February 2023) - Dhakal Adhikari, Shovita; Adhikari, Pawan
ABSTRACT: Applying the ideas of policy diffusion, this paper investigates how anti-child trafficking policies and frameworks have been diffused in Nepal, and critically analyses their implementation in practice. The findings show how different socio-cultural and regulatory factors have either individually or collectively stifled the diffusion trajectory of a comprehensive anti-child trafficking response in Nepal. As a result, anti-child trafficking interventions have been impaired at the implementation stage. The fact that policy diffusion is driven by pro-innovation bias has meant that globally inspired policies and frameworks have fallen short in terms of delivering the intended benefits to the victims and making their voices heard.